Sa Ding Ding’s Wan Wu Sheng : world, pop and buddhist music cross-over / Song Xi Xian - Song, Xi Xian (2015)
Sa Ding Ding is a female pop artist from mainland China known for her success in the world music category. Her music reflects a fusion of Tibetan Buddhist chant, Tibetan folk song and western popular music elements. This dissertation reports an analysis of her music and an investigation into the poises state of composition that highlights the possible categorization of commercial Buddhist music. There is an absent of current research in Buddhist music that focus on Sa and her music. In this study, Sa’s Wan Wu Sheng was selected as a case for analysis. Both musical elements and extra-musical elements were examined. Methodology includes literature review, virtual fieldwork, interview, listening analysis, score analysis, and video analysis. The outcome reveals a heavy use of Tibetan Buddhist chant and Sanskrit text, including visual images that portray Buddhist elements that can be categorized under commercial Buddhist music.